2010
DOI: 10.1177/0013161x10378689
|View full text |Cite
|
Sign up to set email alerts
|

Occupying the Principal Position: Examining Relationships Between Transformational Leadership, Social Network Position, and Schools’ Innovative Climate

Abstract: Throughout the world, educational policy makers, practitioners, and scholars have acknowledged the importance of principal leadership in the generation and implementation of innovations. In many studies, transformational leadership has emerged as a promising approach in response to increasing demands to develop and implement innovations in schools. Although research has suggested that having access to leaders with expertise can significantly stimulate innovation, the link between transformational leadership an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
193
0
23

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(243 citation statements)
references
References 107 publications
(119 reference statements)
8
193
0
23
Order By: Relevance
“…On the one hand, vertical transformational leadership behaviors appear to stimulate team learning on innovative tasks. Moolenaar et al (2010) found that such behaviors supported secondary school teachers' recognition of innovative task features and their sense of urgency and willingness to collectively develop new knowledge. Furthermore, vertical transformational leadership behaviors appear to support team learning via promoting team psychological safety and team efficacy.…”
Section: The Role Of Team Leadership Behavior In Supporting Universitmentioning
confidence: 88%
“…On the one hand, vertical transformational leadership behaviors appear to stimulate team learning on innovative tasks. Moolenaar et al (2010) found that such behaviors supported secondary school teachers' recognition of innovative task features and their sense of urgency and willingness to collectively develop new knowledge. Furthermore, vertical transformational leadership behaviors appear to support team learning via promoting team psychological safety and team efficacy.…”
Section: The Role Of Team Leadership Behavior In Supporting Universitmentioning
confidence: 88%
“…Third, most studies of PLCs acknowledge the importance of stimulating and participative leadership as a key dimension that is part of the organizational capacity that fosters PLCs. This dimension refers to the degree to which school and departmental leaders support and stimulate teacher learning, delegate responsibilities, and share leadership functions (Geijsel, Sleegers, Stoel, & Krüger, 2009;Geijsel, Sleegers, Van den Berg, & Kelchtermans, 2001;Mitchell & Sackney, 2000;Moolenaar, Daly, & Sleegers, 2010;Mulford et al, 2004;Spillane, 2006;Spillane & Kim, 2012;Visscher & Witziers, 2004). Together, the three capacities (personal, interpersonal, and organizational) and their eight underlying dimensions form a conceptual model of PLCs that we will use to test the multidimensional, multilevel nature of PLCs within Dutch elementary schools.…”
Section: Modeling the Plc As A Multidimensional Multilevel Conceptmentioning
confidence: 99%
“…Litwin and Stringer (1968) stated that Organizational Climate as a relatively enduring quality of the internal environment that is experimental by its members, influence their behavior and can be described in terms of the values of a particular set of characteristics of the organization. According to Moolenaar (2010) transformational leadership helps to attain innovative organizational climate and motivates followers in line with the works of (Bass, 1985). Phothong (2016) found that there is relationship between leadership and work climate.…”
Section: Literature Reviewmentioning
confidence: 99%